PEMBERIAN TEPUNG BONGGOL PISANG KEPOK FERMENTASI DAIAM PAKAN TERNAK BABI FASE GROWER DAN EFEKNYA TERHADAP KECERNAAN NUTRIEN (Inclusion of fermented kepok banana corm in the growing pigs diet and its effects on the nutrient digestibility) - Sabarta sembiring; Pratiwi Trisunuwati; Osfar Sjofjan; Irfan H. Djunaidi (Universitas Nusa Cendana, 2020)
This study aimed at investigation the effects of kapok banana corm fermented with Saccharomyces cerevisiae and Aspergillus niger of a compound feed growing pigs on nutrient digestibility. Sixteen crossbred growing pigs Duroc x Landrace, (10 weeks of age; initial body weight 27 ± 3.92 kg) were allotted into four treatments in a randomized block design. There were four treatments diets offered: basal diets without corm fermented feeds (RO); basal diets + 7% corm fermented feeds (R1); basal diets + 14% corm fermented feeds (R2); basal diets + 21% corm fermented feeds (R3). Inclusion of 21% corm fermented feeds in the diet of pigs significantly reduced (P <0.01) dry matter intake and organic matter compared to the control diet. There were no significant different between 14% and 21% corm fermented feeds on the intake and digestibility of dry matter and organic matter of the pigs. However, inclusion of corm fermented feeds at the level of 7% showed the optimum digestibility of dry matter, organic matter, crude protein, and energy with the average value of 66.57%, 70.48%, 83.43% and 70.76%, respectively. It can be concluded that inclusion of corm fermented feeds as compound diet at the level of 7% increased dry matter digestibility and organic matter.